Internet Platforms' Threats: Facebook, Google, etc. - James Alleman (International Telecommunications Society (ITS), 2018)
Free!! Google and Facebook!!! We all know them, what to worry about? Everything! The giants of the internet are expanding into every corner of the economy, politics and our lives. They control the majority of digital advertising; Alphabet, Google's parent, and Facebook receive more than 60 percent of digital advertising revenue (Media Buying 2017); Google controls over 90 percent of search on the web (Statcounter 2017); Facebook and Google represent 40% of consumption of digital content (Economist 2017c). Facebook dominates the social media market (Galloway 2017, p. 96); Amazon has nearly 40 percent of online Xmas sales and is destroying the traditional retail outlets (Galloway 2017, p. 28). Apple earns over 90 percent of smart phone profits, although it has less than 20 percent of the market (Galloway 2017, p. 75). This paper will examine the threat to social order and democracy posed by Facebook and Google, as well as others in the internet space. Facebook, and Google have control over what information and news we receive though "black-box" algorithms; they select what "we need." In addition, these platforms have not taken significant measures to address "fake-news", bots, trolls, or other malicious software on the internet. Indeed, they make money off the proliferation of this misinformation. For example, even by its own calculation, "Facebook has estimated that Russian content on its network, including posts and paid ads, reached 126 million Americans, around 40% of the nation's population." (Economist 2017c) Up to 60 million Facebook accounts are fake, according to its own estimate (Shane and Isaac 2017). And according to the Economist (2017c), in the United States' presidential campaign, one out of every five political messages was posted by robots (bots) on Twitter. FANGs have a business models which encourages this type of practice (Shane and Isaac 2017). These models are designed to maximize growth and maintain users. Thus, they involve easy sign up, lack of verification of authenticity; and only, reluctantly, if at all, closing accounts with significant cause (Shane and Isaac 2017, Zittrain 2014). This paper will examine these issues in depth.
Keywords: K21; L1; L2; L4; L5; L9; 330; Advertising; Antitrust Policy; Democracy; Elections; Propaganda ICT; Internet Platforms; Political Economy